2015
DOI: 10.1128/aem.03295-14
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Survival in, and Release from, White-Tailed Deer Feces

Abstract: White-tailed deer are an important reservoir for pathogens that can contribute a large portion of microbial pollution in fragmented agricultural and forest landscapes. The scarcity of experimental data on survival of microorganisms in and release from deer feces makes prediction of their fate and transport less reliable and development of efficient strategies for environment protection more difficult. The goal of this study was to estimate parameters for modeling Escherichia coli survival in and release from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…E. coli is not ubiquitous in agricultural environments, as it is typically introduced through manure or animal feces. E. coli detected on deer pellets grew at maximal rates at 20°C rather than at 4°C or 35°C, with minimal growth observed at 4°C (35); this is consistent with the results of E. coli survival studies in dairy manure (36) and cattle feces (37). Higher water content has also been associated with a decrease in microbial die-off rates in soil (38).…”
Section: Discussionsupporting
confidence: 79%
“…E. coli is not ubiquitous in agricultural environments, as it is typically introduced through manure or animal feces. E. coli detected on deer pellets grew at maximal rates at 20°C rather than at 4°C or 35°C, with minimal growth observed at 4°C (35); this is consistent with the results of E. coli survival studies in dairy manure (36) and cattle feces (37). Higher water content has also been associated with a decrease in microbial die-off rates in soil (38).…”
Section: Discussionsupporting
confidence: 79%
“…Many pollutan factors could influence the contamination in drinking water. According to Guber et al [10] the parameters of the survival and release models obtained for E. coli in their study were substantially different from those obtained using other sources, such as domestic animal feces and manures. A comprehensive study is needed to get the better predictions.…”
Section: Environmental Contaminationmentioning
confidence: 68%
“…However, information is relatively scarce on release rates from wildlife animal waste. In a recent study, Guber et al (2015) reported drastic differences in E. coli release rates from feces of white-tailed deer compared with E. coli release rates from dairy cattle slurry that had been measured in another study (Guber et al, 2013). Wildlife animal waste comes in widely varying consistencies (Kiefer et al, 2012), and one should expect large variations in release rates, which need to be evaluated.…”
Section: Discussionmentioning
confidence: 99%